Design of two-pass swage autofrettage processes of thick-walled cylinders by computer modeling. (February 2019) - Hu, Zhong
An ever-increasing industrial demand for pressurized thick-walled cylindrical components drives research and practice to increase their strength–weight ratio, extend their fatigue life, or to increase their pressure-carrying capacity. This can be achieved through an energy-efficient and safe two-pass swage autofrettage process by generating a favorable compressive residual hoop stress field in the inner layer of the cylinder prior to use. In this paper, a two-pass swage autofrettage process of a thick-walled cylinder was systematically investigated based on finite element analysis. A 105 mm cannon barrel made of high-pressure vessel steel ASTM A723-1130 was taken as a case study. An elastic nonlinear-hardening plastic material model with the Bauschinger effect was adopted. The mandrel's axial pushing forces during swage autofrettage processes were analyzed. A 30–35% reduction in mandrel's pushing forces has been achieved in the two-pass process. The residual stresses in swage autofrettaged thick-walled cylinders were predicted. The results of computer modeling were in agreement with neutron diffraction measurements. A maximum 18% reduction in von Mises stress in the swage autofrettaged thick-walled cylinders under an elastic-limit working pressure was identified. A maximum 31% increase in pressure-carrying capacity for the swage autofrettaged thick-walled cylinders was revealed. The optimum radial interference was proposed. Results from the two-pass process were compared with those from the single-pass process.